The physicality of leadership gesture, entanglement, taboo, possibilities - Ladkin, Donna; Taylor, Steven S., 1960- (Emerald, 2014)
Colloquially we know that how leaders present themselves physically matters; and those taking up the leader role know this too. Otherwise why would Margaret Thatcher have insisted on standing on a step-stool when speaking publicly, or why would FDR have so carefully downplayed his reliance on his wheelchair? Yet the academic literature has to a large extent ignored this feature of leadership, relegating it to 'below the radar' or in the margins of what is considered to be a 'proper' focus of study. This volume addresses this oversight by inviting leadership scholars from around the world to inquire rigorously into the physical aspect of leading and leadership. In doing so, it brings into high relief aspects of leadership which are often ignored: its gestural and performative nature, the way our physical bodies both enable and constrain the type of leader we can be, the sheer physical demands of taking up the leading role. Most importantly, by noticing and dwelling with the visible facets of leading which are so often overlooked, the book suggests new possibilities for how leadership can be both created and studied.
Keywords: Business & Economics -- Management.; Business & Economics -- Leadership.; Management: leadership & motivation.; Management & management techniques.; Business & management.; Leadership.; Body language.; elektronické knihy; electronic books